Quantifying the Growth History of Seismically Imaged Normal Faults - Osagiede,EE; Duffy,OB; Jackson,CA-L; Wrona,T (Journal of Structural Geology, 2014)
Throw-depth profiles and expansion index plots are typically used to constrain the growth history of seismically imaged normal faults. However, the ability to accurately correlate displaced stratigraphic horizons across faults and hence constrain stratigraphic thickness changes is typically limited by the vertical resolution of, and noise within, the seismic reflection dataset. Vertical seismic resolution is a function of seismic velocities and the source wavelet frequency used during data collection. Here, we test how variations in source wavelet frequency and seismic noise influence imaging of normal faults, and our ability to determine the fault growth history from the construction of throw-depth profiles and expansion index plots. To achieve this, two input models were developed to mimic the geometry and growth history of polycyclic growth faults and blind normal faults. These models provided an input for a series of 2D seismic forward models from which we produced synthetic seismic profiles. The models were run at different peak frequencies and seismic noise levels, so as to mimic variations in seismic data quality associated with changes in the depth of burial. Throw-depth profiles and expansion index plots were derived from the synthetic seismic profiles and used to constrain the fault kinematics, and these results were compared to those derived from the input models. Our results indicate that, at lower peak frequencies and higher seismic noise levels, fault height can be underestimated, and strikingly, that the fault growth history can be misinterpreted. The results of our study indicate that geologists need to be aware of the imaging resolution of seismic reflection data when using these data to determine fault growth history of normal faults. Furthermore, hydrocarbon explorationists should be aware that seismic reflection data, the principal exploration tool, may not allow accurate determination of fault length and height, which may impact risking of hydro